Sodium citrate modified iron-doped hydroxyapatite adsorbent as well as preparation method and application thereof

Iron-doped hydroxyapatite was prepared by co-precipitation method and citrate was introduced for modification, which solved the high material cost and agglomeration problems in cadmium wastewater treatment, and achieved the effect of efficient cadmium removal and simplified preparation process.

CN119657085APending Publication Date: 2025-03-21SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411923781.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when treating cadmium wastewater at different concentrations, the material cost is high and it is difficult to effectively remove cadmium, and the aggregation problem of nano-hydroxyapatite in water bodies has not been effectively solved.

Method used

Iron-doped hydroxyapatite was prepared by co-precipitation method, and the material dispersion and degradation rate were improved by introducing citrate and adsorption and binding of iron-doped nanohydroxyapatite.

Benefits of technology

It significantly improves the efficiency of cadmium removal, improves the maximum adsorption, simplifies the preparation process, reduces material costs, and improves the degradation rate of the material in the soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657085A_ABST
    Figure CN119657085A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium citrate modified iron-doped hydroxyapatite adsorbent as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a Fe < 3 + > solution and a Ca < 2 + > solution to obtain a mixed solution, simultaneously dropwise adding the mixed solution and a PO4 < 3-> solution into an OH <-> solution, stirring to obtain a suspension, filtering the suspension to obtain a precipitate, washing and drying to obtain iron-doped hydroxyapatite; and adding the iron-doped hydroxyapatite into the sodium citrate solution, stirring, centrifuging, and drying in vacuum to obtain the sodium citrate modified iron-doped hydroxyapatite adsorbent. According to the method, firstly, iron-doped hydroxyapatite is prepared by adopting a coprecipitation method, then citric acid radicals are introduced to be combined with iron-doped nano hydroxyapatite in an adsorption manner, and due to the introduction of ferric ions and the citric acid radicals, not only can the cadmium-polluted water be well repaired, but also the dispersity and degradation speed of the hydroxyapatite are greatly improved. The method is easy to operate, low in cost, mild in operation condition and free of the risk of secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water pollution control, and in particular to a sodium citrate-modified iron-doped hydroxyapatite adsorbent and a preparation method and application thereof. Background Art

[0002] With the continuous deepening of industrialization, the problem of heavy metal pollution has become more and more serious. In particular, the wastewater discharge from industries such as mining, electroplating, smelting and battery manufacturing has led to a large amount of cadmium-containing wastewater entering the environment, posing a serious threat to ecological balance and human health. Cadmium is a heavy metal with high mobility, strong bioaccumulation and high toxicity. Its long-term accumulation in the environment can cause serious health problems. Cadmium enters the human body through the food chain. Long-term intake can cause kidney damage, osteomalacia and other diseases, and even affect fertility, leading to an imbalance in the sex ratio.

[0003] Among many wastewater purification technologies, adsorption method is favored due to its advantages such as simple operation, low cost and high treatment efficiency. 10 (PO 4 ) 6 (OH) 2 As a natural mineral and the main component of human bones, nanohydroxyapatite (nHAP) is considered to be an ideal cadmium adsorbent due to its low solubility and high adsorption capacity. Through mechanisms such as ion exchange, surface complexation and dissolution precipitation, nHAP can effectively capture inorganic pollutants and heavy metal ions in water. Xu Huanyan et al. (Study on the removal behavior and mechanism of cadmium ions in aqueous solution by apatite [D]. Guangdong: Sun Yat-sen University, 2004) synthesized hydroxyapatite (HAP) by sol-gel method. At room temperature and pressure, 1 g / L apatite was used to treat 1 mg / L cadmium solution with pH 7. The removal rate reached 99% after 30 minutes of adsorption. When 5 g / L HAP is used to treat a cadmium solution with an initial concentration of less than 10 mg / L and a pH value of 6, the cadmium-containing water sample can reach the comprehensive sewage discharge standard of 0.1 mg / L (GB8978-1996) and even the drinking water sanitation standard of 0.01 mg / L (GB5749-85) after 5 minutes of action. 3+ Materials were composited, and the research showed that the cadmium removal performance could be significantly improved. Gong Hangyuan (Study on the stabilization and remediation of soil lead, cadmium and arsenic composite pollution by iron-doped hydroxyapatite [D]. Central South University, 2022.DOI:10.27661 / d.cnki.gzhnu.2022.004381) et al. prepared nanoscale iron-doped hydroxyapatite (Fe-HAP) by ultrasound-microwave assisted hydrothermal one-step method, which could significantly improve the cadmium removal performance. 2+ 、Cd2+ The adsorption capacities of nHAP and As(V) reached 720 mg / g, 223.25 mg / g and 46.37 mg / g respectively. Although the adsorption performance of HAP has been improved, the agglomeration problem of nHAP in water bodies has not been solved. In order to solve the agglomeration of materials and further improve the cadmium removal performance of materials, studies have been conducted to reduce the surface energy of materials by loading with organic acids, thereby reducing the agglomeration of materials, and the chelation adsorption of organic acid radicals can improve the cadmium removal performance of materials, thereby achieving a double effect and being regarded as an effective modification. However, the modification methods and modification steps are complicated and numerous, making the modification difficult. At present, few studies have considered applying adsorption materials to treat cadmium solutions of different concentrations from the perspective of the actual needs of sewage discharge, so as to save material costs while meeting the cadmium concentration discharge standards of water bodies. Therefore, it is still necessary to continue to modify nHAP, and obtain adsorption materials that can treat cadmium-containing wastewater of different concentrations through simple preparation. Summary of the invention

[0004] In view of the above-mentioned prior art, the purpose of the present invention is to provide a sodium citrate modified iron-doped hydroxyapatite adsorbent and its application in cadmium adsorption. The present invention firstly prepares iron-doped hydroxyapatite by coprecipitation method, and then introduces citrate to combine with iron-doped nano-hydroxyapatite for adsorption. The introduction of trivalent iron ions and citrate can not only well repair cadmium-contaminated water bodies, but also greatly improve the dispersibility and degradation rate of hydroxyapatite in soil.

[0005] To achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a method for preparing a sodium citrate-modified iron-doped hydroxyapatite adsorbent, comprising the following steps: (1) Fe 3+ Solution and Ca 2+ The solutions are mixed to obtain a mixed solution, and the mixed solution and PO 4 3- The solution was simultaneously added with OH - The solution is stirred to obtain a suspension, the suspension is filtered to obtain a precipitate, and the precipitate is washed and dried to obtain iron-doped hydroxyapatite; (2) Adding the iron-doped hydroxyapatite obtained in step (1) into a sodium citrate solution and stirring, centrifuging and vacuum drying to obtain a sodium citrate-modified iron-doped hydroxyapatite adsorbent.

[0006] Preferably, in step (1), the Fe 3+ Fe in solution 3+ The concentration of Ca is 0.1-1.0 mol / L; 2+ The concentration of the solution is 1 mol / L; the PO 4 3-The concentration of the solution is 0.6 mol / L; the OH - The concentration of the solution is 1.4 mol / L.

[0007] Preferably, in step (1), Fe 3+ With Ca 2+ The molar ratio of Ca 2+ Solution, PO 4 3- Solution and OH - The volume ratio of the solution is 1:1:2.

[0008] Preferably, in step (1), the Fe 3+ The solution is at least one of a ferric chloride solution or a ferric sulfate solution; the Ca 2+ The solution is a calcium nitrate solution; the PO 4 3- The solution is a sodium dihydrogen phosphate solution; the OH - The solution is sodium hydroxide solution.

[0009] Preferably, in step (1), the droplet speed of the mixed solution is 15 mL / min; 4 3- The solution was added at a rate of 15 mL / min.

[0010] Preferably, in step (1), the stirring is performed at room temperature for 2 to 4 hours; and the stirring rate is 300 to 1000 r / min.

[0011] Preferably, in step (2), the concentration of the sodium citrate solution is 0.025 mol / L; and the ratio of the added amount of the iron-doped hydroxyapatite to the added amount of sodium citrate is 0.5 g:0.005 mol.

[0012] Preferably, in step (2), the stirring is performed at room temperature for 12 to 48 hours; the stirring rate is 300 to 1000 r / min.

[0013] The second aspect of the present invention provides a sodium citrate-modified iron-doped hydroxyapatite adsorbent obtained by the above preparation method.

[0014] The third aspect of the present invention provides the use of a sodium citrate-modified iron-doped hydroxyapatite adsorbent in any one of the following 1) to 3): 1) Improve the adsorption and removal rate of cadmium; 2) Improve the dispersibility of hydroxyapatite; 3) Increase the degradation rate of hydroxyapatite.

[0015] Beneficial effects of the present invention: (1) The iron-doped hydroxyapatite prepared by the present invention is synthesized by a one-step method. By introducing trivalent iron ions to load and dope hydroxyapatite, the removal efficiency of cadmium is significantly improved and the maximum adsorption capacity is increased. It can be applied to cadmium-contaminated water bodies, and the application method is simple and can effectively remove cadmium.

[0016] (2) The present invention uses an in-situ adsorption method to modify the iron-doped hydroxyapatite nanocomposite material to obtain a sodium citrate-modified iron-doped hydroxyapatite adsorbent. The introduced citrate is adsorbed and combined with the iron-doped nanohydroxyapatite. The surface properties of the modified material can be well targeted at the repair of cadmium-contaminated water bodies. And because the citrate, trivalent iron ions and hydroxyapatite are all biodegradable, the product obtained after degradation is not only harmless to the environment, but also can provide nutrients for plant growth and improve the soil environment when used for irrigation of the treated water body.

[0017] (3) The preparation of the sodium citrate-modified iron-doped hydroxyapatite adsorbent of the present invention is carried out at room temperature, with simple operation, low cost, mild operating conditions, and no risk of secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : SEM images of Fe-nHAP, where (a) is the SEM image of 0% Fe-nHAP, (b) is the SEM image of 10% Fe-nHAP, (c) is the SEM image of 30% Fe-nHAP, (d) is the SEM image of 50% Fe-nHAP, and (e) is the SEM image of 100% Fe-nHAP; Figure 2 : Fourier transform infrared spectra of Fe-nHAP prepared in Example 1 and Comparative Example 1; Figure 3 : X-ray diffraction spectra of Fe-nHAP prepared in Example 1 and Comparative Example 1; Figure 4 : Element contents of Fe-nHAP prepared in Example 1 and Comparative Example 1; Figure 5 : Infrared spectra of 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, pure nHAP and commercial nHAP (C-nHAP) before (a) and after (b) adsorption of Cd; Figure 6 : X-ray diffraction spectra of 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, pure nHAP and commercial nHAP (C-nHAP) before (a) and after (b) adsorption of Cd; Figure 7: Dispersibility of 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, and S-nHAP-2, S-nHAP-3, and S-nHAP-4 prepared in Comparative Example 2 in solution; Figure 8 : The adsorption effects of 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, and S-nHAP-2, S-nHAP-3, and S-nHAP-4 prepared in Comparative Example 2 in low concentration cadmium solution; Fig. 9 : The adsorption effects of 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, and S-nHAP-2, S-nHAP-3, and S-nHAP-4 prepared in Comparative Example 2 in high concentration cadmium solution. DETAILED DESCRIPTION

[0019] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0020] As described in the background technology section, doping with trivalent iron ions can improve the adsorption energy of nHAP for heavy metals, but the doping of trivalent iron ions is uneven, and the improvement of adsorption capacity is limited. In addition, doping with trivalent iron ions cannot overcome the problem of poor dispersibility of nHAP.

[0021] Based on this, the purpose of the present invention is to provide a sodium citrate modified iron-doped hydroxyapatite adsorbent and its application in cadmium adsorption. The present invention first adopts coprecipitation method to prepare iron-doped hydroxyapatite. In view of the combination of metal cations with phosphate and hydroxide when hydroxyapatite unit nucleus is formed, the introduced trivalent iron ions compete with calcium ions for binding phosphate and hydroxide, and after entering the insoluble phosphate lattice attached with hydroxide, the trivalent iron ions can be continuously and slowly released step by step, which can be well targeted at the repair of cadmium-contaminated water bodies. And because hydroxyapatite lime is biodegradable, the products obtained after degradation are phosphate ions and calcium ions, which are not only harmless to the environment, but also can provide nutrients for plant growth and improve the soil environment for the water body after treatment for irrigation. The content of trivalent iron in coprecipitation cannot be too high or too low, otherwise it will affect the competitive balance with calcium ions, and then affect the adsorption performance of iron-doped hydroxyapatite. Then, the present invention adopts the in-situ adsorption method again, and sodium citrate is utilized to modify iron-doped hydroxyapatite, and the citrate introduced is combined with iron-doped nano-hydroxyapatite adsorption, and the surface property of the modified material can be well directed to the repair of cadmium-contaminated water bodies, and the dispersibility of iron-doped hydroxyapatite is improved. The content of citrate is not that the more the better, and for 0.5g iron-doped hydroxyapatite, adding 0.005mol of sodium citrate for modification effect is the best, and after the addition amount of sodium citrate increases, not only the adsorption capacity of the modified adsorbent decreases, but also dispersibility is improved. And because citrate, trivalent iron ion and hydroxyapatite are all biodegradable, the product obtained after degradation is not only harmless to the environment, but also can provide nutrients for plant growth for irrigation to the water body after treatment, and improves the soil environment.

[0022] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0023] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0024] Example 1: Preparation of iron-doped hydroxyapatite Prepare 100mL of 1mol / L calcium nitrate solution and add 100mL of 0.5mol / L ferric chloride solution to obtain an iron-calcium mixed solution, namely Fe 3+ With Ca 2+The molar ratio is 1:2 (50%). Prepare 100mL of 0.6mol / L sodium dihydrogen phosphate solution and 200mL of 1.4mol / L sodium hydroxide solution; add calcium iron mixed solution and sodium dihydrogen phosphate solution to the sodium hydroxide solution at the same flow rate (15mL / min) through a peristaltic pump, adjust the stirring speed to 500r / min, stir at room temperature for 2h and then stand for 1h; centrifuge the lower precipitate and repeatedly wash the precipitate with ultrapure water; dry it in a vacuum drying oven at 60°C for 24h to obtain iron-doped hydroxyapatite, recorded as 50%Fe-nHAP.

[0025] Example 2: Preparation of sodium citrate-modified iron-doped hydroxyapatite adsorbent Prepare 200 mL of 0.025 mol / L sodium citrate solution (i.e., add 0.005 mol sodium citrate), add 0.5 g of the iron-doped nano-hydroxyapatite prepared in Example 1, adjust the stirring speed to 500 r / min, and stir at room temperature for 24 h; centrifuge the powder material and dry it in a vacuum drying oven at 60° C. for 24 h to obtain a sodium citrate-modified iron-doped hydroxyapatite adsorbent, recorded as S-nHAP.

[0026] Comparative Example 1 The difference from Example 1 is that Fe 3+ With Ca 2+ The molar ratios of Fe-nHAP and Fe-nHAP are 0:2 (0%), 0.2:2 (10%), 0.6:2 (30%), and 2:2 (100%). The iron-doped hydroxyapatites finally prepared are recorded as 0%Fe-nHAP, 10%Fe-nHAP, 30%Fe-nHAP, and 100%Fe-nHAP according to the iron doping amount.

[0027] Comparative Example 2 The difference from Example 2 is that 0.01 mol, 0.015 mol and 0.03 mol of sodium citrate were added. Finally, sodium citrate-modified iron-doped hydroxyapatite adsorbents were prepared and recorded as S-nHAP-2, S-nHAP-3 and S-nHAP-4 respectively.

[0028] Comparative Example 3 Prepare 200 mL of 0.025 mol / L sodium citrate solution (i.e., add 0.005 mol sodium citrate), add 0.5 g of nano-hydroxyapatite (nHAP), adjust the stirring speed to 500 r / min, and stir at room temperature for 24 h; centrifuge the precipitate and dry it in a vacuum drying oven at 60 °C for 24 h to obtain a powder material, i.e., sodium citrate-modified hydroxyapatite adsorbent, recorded as S-0%Fe-nHAP.

[0029] Characterization: (1) The Fe-nHAP prepared in Example 1 and Comparative Example 1 was characterized by scanning electron microscopy (SEM). Figure 1 As shown. From the figure, the particle sizes of the five Fe-nHAPs are approximately 27, 35, 58, 62, and 66 nm (0%, 10%, 30%, 50%, and 100% iron doping) calculated by counting. All five materials show agglomeration, and as the amount of iron doping increases, the morphology of the material becomes closer to amorphous. This is because iron doping significantly changes the morphology and crystal growth direction of hydroxyapatite particles. As the amount of iron doping increases, the intensity of the crystal face diffraction peak may be affected, resulting in a decrease in crystallinity, a decrease in grain size, and a decrease in lattice constant, indicating that the lattice shrinks along the c-axis. This change in the direction of crystal growth may lead to an increase in the irregularity of the crystal structure, making the material tend to be amorphous.

[0030] Fourier transform infrared spectroscopy (FT-IR) was used to measure the -1 The functional groups of the material are measured at wave numbers between Figure 2 As shown in the figure, the main absorption peak of Fe-nHAP has not changed significantly, indicating that its group composition is the same. 3400~3700 cm -1 The wavelength range corresponds to the OH bond of the hydroxyl group in Fe-nHAP; 1600~1650 cm -1 The corresponding one is H 2 The absorption peak of O produces bending vibration (H 2 O may come from the absorption of water in the air by Fe-nHAP); at 1350~1500cm -1 The wavelength appears to be CO 3 2- The stretching vibration of the absorption peak is due to the absorption of CO in the air by Fe-nHAP during the preparation process. 2 950~1100 cm -1 and 550-650 cm -1 The left and right sides show the PO in Fe-nHAP. 4 3- The absorption peak is generated by the asymmetric bending vibration of PO 4 3- The splitting or even disappearance of the absorption peak is related to Fe 3+ The doping concentration increases from 10% to 100%. -1 and 632.54 cm -1 The wavelength originally belongs to PO 4 3- The vibration peak may be due to the Fe 3+The 50% Fe-nHAP and 100% Fe-nHAP in PO 4 3- The peak shift and peak intensity reduction of the characteristic peak position are also due to Fe 3+ In summary, the Fe-nHAP powders with various iron content prepared by the present invention all contain CO 3 2- ,PO 4 3- OH - etc. functional groups.

[0031] The Fe-nHAP prepared in Example 1 and Comparative Example 1 was subjected to XRD detection, and the obtained XRD patterns are as follows: Figure 3 The results show that the characteristic peaks of 0% Fe-nHAP match the characteristic peaks of hydroxyapatite phase (JCPDS: 72-1243). After 10%~100% iron doping, nHAP peaks appear or disappear, the diffraction peak position of 2θ angle gradually shifts or disappears, and the peak intensity is also significantly reduced, matching the characteristic peaks of calcium iron phosphate phase (JCPDS: 35-0496), which indicates that with the increase of Fe 3+ The increase of doping amount into the Fe in nHAP lattice 3+ The corresponding increase causes the structure of the HAP crystal itself on the (112), (301), (241), (323) crystal planes to be destroyed, the lattice to be distorted, and the crystallinity to decrease, but the partial structure of the nHAP crystal is still retained, eventually forming a weakly crystalline Fe-nHAP.

[0032] The Fe-nHAP prepared in Example 1 and Comparative Example 1 was completely dissolved in dilute nitric acid, and the iron and calcium contents in the solution were determined by ICP-OES and the P content was determined by UV spectrophotometer. The element contents of the materials were calculated as follows: Figure 4 As shown in the figure, with the increase of iron doping, the calcium content gradually decreases, while the P content of the five materials tends to a stable value, indicating that calcium and iron form the crystal nucleus of the material by competing with each other on the phosphate. At different iron doping ratios of 10% to 100%, the element content was determined to prove the synthesis of nHAP materials with the target iron doping ratio, and also showed that Fe was successfully doped into the nHAP lattice to form Fe-nHAP by replacing the Ca binding site.

[0033] (2) The 50% Fe-nHAP prepared in Example 1, the S-nHAP prepared in Example 2, pure nHAP and commercial nHAP (C-nHAP) (purchased from Shanghai Dibai Biotechnology Co., Ltd.; nano-hydroxyapatite, needle-shaped, particle size 60 nm) were measured by Fourier transform infrared spectroscopy (FT-IR). Figure 5In (a), it can be seen that the main absorption peaks of the sodium citrate-modified S-nHAP and the iron-doped 50% Fe-nHAP material before cadmium adsorption have no significant changes compared with nHAP and C-nHAP, indicating that their group compositions are the same. -1 There is a weaker carboxyl group -COO- peak at the peak position. This is because the sodium citrate modification dosage is low (0.005mol:0.5g), resulting in less adsorption of citrate on the material and a weaker peak in the test result. -1 The wavelength range corresponds to the OH bond of the hydroxyl group in the material; 1630cm -1 The corresponding one is H 2 The absorption peak of O produces bending vibration (H 2 O may come from the absorption of water in the air by the material); at 1400-1500cm -1 The wavelength appears to be CO 3 2- The stretching vibration of the absorption peak is due to the absorption of CO in the air by nHAP during the preparation process. 2 At 1350, 1096, 1039, 963, 630, 603 and 563cm -1 The left and right sides show PO in nHAP 4 3- The absorption peak of S-nHAP and 50%Fe-nHAP showed some PO 4 3- The weakening of absorption peaks (1096, 1039, 603, 563 cm -1 ) or even disappear (630 cm -1 ) phenomenon, which is related to Fe 3+ The stretching vibration of the Fe-O bond of S-nHAP and 50%Fe-nHAP showed two main peaks, one at 540-650 cm -1 With PO 4 3- The peaks of the two are overlapping and difficult to distinguish. The other one is located at 400-450 cm -1 The peak shape, position and complexity of this region are largely affected by lattice distortion and structural non-ideality, as well as the different valence states and coordination environments of Fe ions.

[0034] The 50% Fe-nHAP prepared in Example 1, the S-nHAP prepared in Example 2, the pure nHAP and the commercial nHAP (C-nHAP) were subjected to Cd adsorption and then subjected to infrared spectroscopy. The Cd concentration was 10 mg / L and the amount of the adsorbent was 5.4 mg / 45 mL. Figure 5(b) It can be seen that due to the low Cd content, the Cd adsorbed on the material is low, and the detected Cd-O peak overlaps with the Fe-O peak, making it difficult to determine. 4 3- The peak intensity of the peak position showed an increasing trend, while that of nHAP and C-nHAP showed a decreasing trend, which indirectly indicated that the citrate-modified S-nHAP was adsorbed on its surface. When S-nHAP contacted and adsorbed Cd, it first combined with the carboxyl group -COO-, and then made the surface PO 4 3- More sites exposed lead to PO 4 3- The peak intensity increases.

[0035] X-ray diffraction (XRD) was performed on the 50% Fe-nHAP prepared in Example 1, the S-nHAP prepared in Example 2, pure nHAP and commercial nHAP (C-nHAP) to detect their phase compositions. The obtained XRD patterns are shown in FIG. Figure 6 The results show that the characteristic peaks of pure nHAP and C-nHAP (commercially available nanohydroxyapatite) match the characteristic peaks of hydroxyapatite phase (JCPDS: 72-1243). However, after 50% iron doping, the peaks appeared or disappeared, the diffraction peaks at 2θ angle gradually shifted or disappeared, and the peak intensity also decreased significantly, which indicates that with the increase of Fe 3+ The increase of doping amount into the Fe in the HAP lattice 3+ The corresponding increase destroyed the crystal structure of HAP itself, distorted the lattice, and finally formed weak crystalline Fe-nHAP, which matches the physical phase of calcium iron phosphate (JCPDS:35‑0496). At the same time, after sodium citrate modification, the crystal structure of the material was also completely destroyed, similar to 50% Fe-nHAP, but the characteristic peak position was very similar, indicating that the sodium citrate modified material did not destroy the existing crystal form of the material, but on the contrary, it was loaded on the surface of the material to enhance the adsorption of cadmium.

[0036] Test Example 1: Dispersibility Test The hydrodynamic diameter of pure nHAP, 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, S-nHAP-2, S-nHAP-3, S-nHAP-4 prepared in Comparative Example 2, and S-0% Fe-nHAP prepared in Comparative Example 3 were tested. The above materials were placed in ultrapure water (with a concentration of 0.12 g / L) and shaken on a constant temperature shaker for 24 hours. The hydrodynamic diameter (particle size) of the materials was tested by a Zetasizer instrument. The results are shown in Figure 7 .

[0037] according to Figure 7It can be seen that the S-nHAP prepared in Example 2 at a dosage concentration of 0.12 g / L, in 10 min ultrasound and 12 h continuous constant temperature oscillation in ultrapure water, compared with other modified dosages, the hydrodynamic diameter of S-nHAP at a dosage of 0.005 mol: 0.5 g was reduced from 381 nm to 265 nm, and the Zeta potential value in ultrapure water was reduced from -15.8 mv to -32.7 mv, which is because the addition of sodium citrate increases the charge density on the surface of hydroxyapatite nanomaterials, enhances the repulsive force between particles, and thus improves the dispersibility of nanomaterials. Therefore, the S-nHAP in Example 2 has the best dispersibility.

[0038] Test Example 2: Cadmium adsorption test (1) Low concentration cadmium adsorption Low concentration cadmium adsorption test was conducted on pure nHAP, 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, S-nHAP-2, S-nHAP-3, S-nHAP-4 prepared in Comparative Example 2, and S-0% Fe-nHAP prepared in Comparative Example 3. The specific method is: weigh 9 mg of each group of materials and add them to 45 mL of 10 mg / L cadmium solution, shake at a constant temperature of 25°C and 200RPM for 24 hours; take the supernatant and filter to determine the Cd content, and the results are shown in Figure 8 .

[0039] according to Figure 8 It can be seen that the adsorption effect of S-nHAP and S-nHAP-2 of 50% Fe-nHAP modified with low-dose sodium citrate on low-concentration cadmium is slightly increased. The increase is not high because the Cd concentration in the solution is too low, which still shows that the sodium citrate modified material can enhance the adsorption performance of 50% Fe-nHAP. However, as the sodium citrate modification dosage increases to 0.015~0.03mol:0.5g, the adsorption performance of S-nHAP-3 and S-nHAP-4 decreases compared with 50% Fe-nHAP. It can be seen that the amount of sodium citrate added affects the improvement of 50% Fe-nHAP adsorption performance. Therefore, the sodium citrate modification dosage of S-nHAP prepared in Example 2 is the best dosage for enhancing adsorption performance in low-concentration cadmium adsorption.

[0040] (2) High concentration cadmium adsorption High concentration cadmium adsorption was tested for pure nHAP, 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, S-nHAP-2, S-nHAP-3, S-nHAP-4 prepared in Comparative Example 2, and S-0% Fe-nHAP prepared in Comparative Example 3. The specific method is: weigh 9 mg of material and add it to 45 mL of 300 mg / L cadmium solution, shake it at a constant temperature of 25°C and 200 RPM for 24 hours; take the supernatant and filter it to determine the Cd content. The results are shown in Fig. 9 .

[0041] according to Fig. 9 It can be seen that the adsorption performance of 50% Fe-nHAP materials modified with sodium citrate at four dosages has been further improved for high concentration cadmium, indicating that sodium citrate modified materials can enhance their adsorption performance. Among them, S-nHAP modified with a dosage of 0.005mol:0.5g has the best adsorption performance, and the adsorption amount and removal rate are the largest compared with 50% Fe-nHAP, which are increased by 28.75% (adsorption amount) and 29.69% (removal rate) respectively. Interestingly, compared with the low-concentration adsorption performance, the adsorption performance of S-nHAP-3 and S-nHAP-4 in high-concentration cadmium solution has been improved. This may be because the adsorbate in the high-concentration cadmium solution is sufficient, and the citrate loaded on the S-nHAP-3 and S-nHAP-4 materials can completely combine with Cd, so that the original adsorption sites of the 50% Fe-nHAP covered or blocked by them are exposed, and can further combine with the cadmium in the solution. Therefore, the adsorption performance of S-nHAP-3 and S-nHAP-4 is improved compared with 50% Fe-nHAP in high-concentration cadmium solution. However, the adsorption amount and removal efficiency are still lower than those of the S-nHAP prepared in Example 2. Therefore, the sodium citrate modification dosage of the S-nHAP prepared in Example 2 is the best dosage to enhance the adsorption performance in high-concentration cadmium adsorption.

[0042] Test Example 3: Biodegradability Test Pure nHAP, 50% Fe-nHAP prepared in Example 1, S-nHAP prepared in Example 2, S-nHAP-2, S-nHAP-3, S-nHAP-4 prepared in Comparative Example 2, and S-0% Fe-nHAP prepared in Comparative Example 3 were buried 5 cm below the soil at an addition amount of 50 g P / kg. The total P concentration in the soil was detected to be 1.04 g / kg before burial. 30 days after burial, the sampled soil was completely digested with an acidic reagent and the phosphate concentration in the supernatant was measured using a UV-Vis spectrometer (GENESYS 50, Thermo Fisher Scientific, USA) at 880 nm absorbance, and the total P content was calculated, and the difference before and after burial of each group was calculated. The results are shown in Table 1.

[0043] Table 1 Degradation of each group The degradation rate of each group of materials can be seen from the increase in the total P concentration in the soil: the P generated by the degradation of hydroxyapatite enters the soil, and the difference in P concentration before and after burial is calculated. The larger the difference, the faster the degradation rate of hydroxyapatite. According to Table 1, it can be seen that the degradation rate of S-nHAP is not only much higher than that of the pure nHAP group, the 50% Fe-nHAP group and the S-0% Fe-nHAP group, but also higher than that of the S-nHAP-2, S-nHAP-3, and S-nHAP-4 groups. It shows that the S-nHAP prepared by the present invention can improve the degradation rate of nHAP in the soil.

[0044] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a sodium citrate-modified iron-doped hydroxyapatite adsorbent, characterized in that: The following steps are involved: (1) Fe 3+ Solution and Ca 2+ The solutions were mixed to obtain a mixed solution, and the mixed solution and PO4 3- The solution was simultaneously added with OH - The solution is stirred to obtain a suspension, the suspension is filtered to obtain a precipitate, and the precipitate is washed and dried to obtain iron-doped hydroxyapatite; (2) Adding the iron-doped hydroxyapatite obtained in step (1) into a sodium citrate solution and stirring, centrifuging and vacuum drying to obtain a sodium citrate-modified iron-doped hydroxyapatite adsorbent.

2. The preparation method according to claim 1, characterized in that: In step (1), the Fe 3+ Fe in solution 3+ The concentration of Ca is 0.1-1.0 mol / L; 2+ The concentration of the solution is 1 mol / L; the PO4 3- The concentration of the solution is 0.6 mol / L; the OH - The concentration of the solution is 1.4 mol / L.

3. The preparation method according to claim 1, characterized in that: In step (1), Fe 3+ With Ca 2+ The molar ratio of Ca 2+ Solution, PO4 3- Solution and OH - The volume ratio of the solution is 1:1:

2.

4. The preparation method according to claim 1, characterized in that: In step (1), the Fe 3+ The solution is at least one of a ferric chloride solution or a ferric sulfate solution; the Ca 2+ The solution is a calcium nitrate solution; the PO4 3- The solution is a sodium dihydrogen phosphate solution; the OH - The solution is sodium hydroxide solution.

5. The preparation method according to claim 1, characterized in that: In step (1), the drop rate of the mixed solution is 15 mL / min; the PO4 3- The solution was added at a rate of 15 mL / min.

6. The preparation method according to claim 1, characterized in that: In step (1), the stirring is performed at room temperature for 2 to 4 hours; the stirring rate is 300 to 1000 r / min.

7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the sodium citrate solution is 0.025 mol / L; the ratio of the added amount of the iron-doped hydroxyapatite to the added amount of sodium citrate is 0.5 g:0.005 mol.

8. The preparation method according to claim 1, characterized in that: In step (2), the stirring is carried out at room temperature for 12 to 48 hours; the stirring rate is 300 to 1000 r / min.

9. The sodium citrate-modified iron-doped hydroxyapatite adsorbent obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the sodium citrate modified iron-doped hydroxyapatite adsorbent according to claim 9 in any one of the following 1) to 3): 1) Improve the adsorption and removal rate of cadmium; 2) Improve the dispersibility of hydroxyapatite; 3) Increase the degradation rate of hydroxyapatite.